Experimental Implementation of a Low-Cost Single Phase Five-Level Inverter for Autonomous PV System Applications Without Batteries - Nouaiti, A.; Saad, A.; Mesbahi, A.; Khafallah, M. (Engineering, Technology & Applied Science Research, 2018)
This paper presents the design and the implementation of a low-cost single phase five-level inverter for photovoltaic applications. The proposed multilevel inverter is composed of a simple boost converter, a switched-capacitor converter, and an H-bridge converter. An efficient control method which associates a closed-loop regulation method with a simple maximum power point tracking (MPPT) method is applied in order to allow the proposed multilevel inverter to transfer power energy from solar panels to autonomous load with no storage batteries. An experimental prototype of this inverter is fabricated at the laboratory and tested with a digital control system. Obtained results confirm the simplicity and the performance of the proposed photovoltaic system.